An Innovative Approach to Addressing the HIV Care Continuum: Implementation of a Clinical Pharmacy Resident in a Veterans Affairs HIV Specialty Clinic. (October 2018) - Bagwell, Autumn; McFarland, M. Shawn; Hulgan, Todd
Purpose: Engagement of patients in the HIV care continuum and adherence to antiretroviral therapy (ART) continue to limit successful viral suppression. Innovative practices to improve this continuum and ameliorate potential physician shortages are needed. The objective of this evaluation was to determine the clinical benefits of incorporating pharmacy resident involvement on a multidisciplinary team in caring for patients with HIV. Methods: A single-center pre–post cohort pilot evaluation was conducted at the Tennessee Valley Healthcare Systems VA Medical Center. Patients were enrolled in an HIV pharmacotherapy clinic implemented by an ambulatory care pharmacy resident. The primary end point of the evaluation was the percentage of patients achieving an undetectable plasma HIV viral load after enrollment. Secondary end points included change from baseline in CD4 T-cell count and self-reported adherence. Results: A total of 55 patients were seen in the HIV pharmacotherapy clinic over a 28-week evaluation period. Of those patients with detectable viral load at enrollment, 70% reached viral suppression during follow-up, with a significant 0.75 log10 decrease in the median viral load ( P < .0001 for both). The median CD4 T-cell count increased from 464 to 525 cells/mm 3 ( P = .01). Reported adherence, assessed using the Visual Analogue adherence Scale (VAS) increased significantly ( P = .0001). Conclusion: After enrollment in an HIV pharmacotherapy clinic, a significant decrease in viral load was seen, as were improvements in secondary end points of CD4 T cells and adherence. These data demonstrate the clinical benefits of pharmacy resident involvement on a multidisciplinary team in caring for patients with HIV.